2001
DOI: 10.1046/j.0306-5251.2001.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased oral ganciclovir bioavailability in HIV‐infected patients with chronic diarrhoea and wasting syndrome—a population pharmacokinetic study

Abstract: Aims  Despite a lack of data, the antiviral agent ganciclovir is not indicated in AIDS patients with diarrhoea because of its presumed poor oral bioavailability. To assess the effect of diarrhoea on ganciclovir intestinal absorption, we conducted a pharmacokinetic study in 42 HIV‐infected patients categorized into three groups: A, HIV stage A and B (n = 15); B, AIDS stage C (n = 13); C, AIDS with chronic diarrhoea and wasting syndrome (n = 14). Methods  Each patient was evaluated for nutritional (body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The results are presented in Table 2 . Four studies included patients with wasting and concomitant diarrhea [ 14 17 ] and are represented separately ( Table 3 ). The remaining five studies [ 18 22 ] correlated pharmacokinetic parameters in patients with chronic disease with parameters of body composition ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are presented in Table 2 . Four studies included patients with wasting and concomitant diarrhea [ 14 17 ] and are represented separately ( Table 3 ). The remaining five studies [ 18 22 ] correlated pharmacokinetic parameters in patients with chronic disease with parameters of body composition ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is no evidence that cachexia influences renal function, although higher incidence of new renal failure after valvular surgery was associated with cardiac cachexia [ 58 ]. The pharmacokinetics of intravenously administered carboplatin, which is eliminated only via kidneys, was not influenced by cachexia [ 11 ] and half-life of another renally excreted drug ganciclovir was also not prolonged in cachectic patients [ 14 ]. However, due to muscle mass loss in cachectic patients, renal function may be overestimated if based on serum creatinine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In the first step of the analysis, the basic pharmacokinetic model without any covariates was defined [5]. The Akaike information criterion (Akaike value = objective function + 2 × P, where P is the number of estimated parameters and the objective function is similar to the function estimated by NONMEM) decreased from 722 for the one‐compartment model to 712 for the two‐compartment model, which indicated that the latter is better than the former model.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these interactions are tested in PK trials performed in healthy volunteers. However, an important concern is that the pharmacokinetics of antiretroviral drugs seem to be different in patients, partly because of a modification of absorption characteristics during HIV infection [11][12][13]. The possibility of performing PK interaction and bioequivalence trials in patients, requiring a reduced number of samples per subject, is therefore of a great importance.…”
Section: Discussionmentioning
confidence: 99%